Dual language intervention in a case of severe speech sound disorder - Ramos, Eliane; Mead, Jean (Revista de Investigación en Logopedia, 2014)
This single case study of a bilingual child with a severe speech sound disorder examined whether language transference occurs when treatment is provided in L1 or L2 and whether monolingual or bilingual intervention is most effective. A 6-year 5-month old sequential Portuguese/English bilingual female was seen for 3 separate intervention phases lasting about 2 months each. Four phonological processes common to both languages were targeted in either monolingual or bilingual conditions in each phase. The child’s speech was examined with formal tests and analyses of spontaneous speech after each phase. Results indicated that transference occurred in both directions for some processes (L1 to L2 and L2 to L1), but in general L1 had to be specifically targeted for significant improvement to occur. For both languages, the bilingual condition was most effective. A follow-up assessment one year after Portuguese treatment was interrupted revealed that the child continued to make progress in English only (the only language treated for the entire year) and her Portuguese phonology still showed the same errors as in the previous year. This case study provides further evidence that bilingual intervention is the preferred choice for bilingual children. Implications for language choice and future studies are discussed.